The environmental dimension in the context of the operations strategy of the São Paulo’s ABC region automotive manufacturers - Scur, Gabriela; Heinz, Guilherme (Review of Business Management, 2016)
Purpose – This paper aims to analyze the insertion of the environmental dimension in the operations strategy of three automotive manufacturers belonging São Paulo’s ABC region, and how it can impact the operations field’s competitive performance. Design/methodology/approach – Descriptive, exploratory multiple case study. Findings – There is an alignment between companies with regard to the performance indicators of the environmental dimension and to competitive priorities. We observed concern as to the social aspect of sustainability. Companies are designing socially fair production systems, in which work safety and occupational health are seen as strategic factors that contribute to competitive performance in the field of operations. Originality/value – One theoretical contribution is the proposal of a conceptual model that aims to fill a gap in literature concerning the lack of alignment between the operations strategy and environmental management, which can, in turn, hinder or even underestimate the understanding of the role of the operations field in the quest for competitive advantage.